Evaluation of normal range of maximum mouth opening for Pune Maharashtra adult population - Vaishali Vasant Koranne; Samir Achyut Joshi; Amod Pramod Patankar; Swapna Amod Patankar (Archives of Medicine and Health Sciences, 2021)
Background and Aim: Maximal mouth opening (MMO) is used as a marker of masticatory pathology. MMO varies with age, height, gender, and race. The current study is an attempt to calculate the normal range of maximum mouth opening in an adult Pune Maharashtra population. Materials and Methods: A total of 800 individuals, 400 males and 400 females, in the age group of 18–60 years attending outpatient department in Bharati Dental College and Hospital, Pune were randomly selected and divided into four groups according to their age ranges. In addition to the basic demographic data, MMO was measured in these individuals. The subjects were asked to open their mouth maximally until no further opening was possible. The distance from the incisal edge of the upper incisor teeth to the incisal edge of the lower incisor teeth was measured using a calibrated fiber ruler. Statistical analysis was performed. Results: The mean MMO for males was 50.58 (standard deviation [SD] ± 2.16) mm (Range 37–56 mm) and for females was 48.29 (SD ± 3.12) mm (Range 36–53 mm). There was a statistically significant difference between the mouth opening of male and female in all the age groups with P < 0.05 A linear relationship was observed between the mouth opening and age in both males and females and the mouth opening decreased as the age increased. In the age group of 18–29 years, the mean MMO was 54.34 (SD ± 1.84) mm. The range was 39–56 mm for males and 51.63 (SD ± 2.33) mm. with range 38–53 mm for females. In the age group of 30–39 years, the mean MMO was 52.09 (SD ± 1.72) (range 38–53 mm) and 50.07 (SD ± 2.09) (range 38–51 mm) for males and females, respectively. For the age group 40–49 years, the mean MMO was 48.94 (SD ± 1.66) mm (range 39–54 mm) for males and 46.73 (SD ± 2.84) mm (range 38–50 mm) for females. In the age group of 50–60 years, the corresponding values for males and females were 46.98 (SD ± 2.04) (range 36–50 mm) and 44.76 (SD ± 2.59) mm (range 36–49 mm). Conclusion: The MMO range for different age groups is established for normal adult Pune Maharashtra population.